Analisa dan Perbandingan Kinerja Routing Protocol OSPF dan EIGRP dalam Simulasi GNS3 - Loka, Gede Andika; Permana, Silvester Dian Handy; Bintoro, Ketut Bayu Yogha (JISA(Jurnal Informatika dan Sains), 2018)
Router is the network equipment for route the packet from one network segment to another in a bigscale network. Router can route packet because there is a routing table in router configuration. Routing table is anaddress list of source and destination address where the packet will be routed. There are two methods of routing tableconfiguration, static routing and dynamic routing. Static routing is a routing table configuration method where all ofrouting table content is configured manually, usually for a small scale of network. Dynamic network is a routing tableconfiguration method by the router automatically, usually for a big scale of network. A dynamic routing is built fromthe routing information collected by the routing algorithm. There are two routing algorithm, link-state and distancevector algorithm. This simulation will be built in GNS3 simulation software. Goal of this research is to compare theperformance between that two algorithm from two routing protocol that using each of those two algorithm. Thecomparison will be running between OSPF routing protocol on the link state routing protocol and EIGRP on thedistance vector routing protocol side. The result of this analysis and comparison of those two routing protocol isexpected to be a reference of choosing better routing protocol in building a network